Preferences of Unemployed Jordanian Youth from their Own Points of View in Light of Low Job Opportunities - Alkhozahe, Hussein Omar; Alhabashneh, Abdulhai Abedalaziz (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aimed at identifying the preferences of unemployed Jordanian youths, in light of low job opportunities, and getting acquainted with the procedures that help to confront unemployment. Methods: This study used the comprehensive social survey method for all (201) youth centers located in all governorates and districts of the Hashemite Kingdom of Jordan. The sample consisted of (5271) males and females who are participating in youth activities focusing on topics, such as political participation and socio-cultural issues, using the simple random sample method. In order to achieve the objectives of the study, a questionnaire consisting of (40) items were developed to indicate the preferences of unemployed youths in the absence of job opportunities, and the procedures and solutions that help to confront unemployment. Results: Most of the preferences of the unemployed are related to accepting work, even if it is in a field different from their specialization, accepting work even if it is temporary, or with low pay. Conclusions: This research recommends cooperation between the government and the private sector to establish an unemployment insurance fund. Also, unemployment rates among young people are rising constantly, and solving it requires rehabilitating and training young people to gain the necessary skills for work and encouraging them to accept job opportunities even if they are not up to their expectations.